2023
DOI: 10.1007/s10804-023-09449-4
|View full text |Cite
|
Sign up to set email alerts
|

Conceptions of Adulthood Among Chinese Emerging Adults

Abstract: With the in uence of globalization, Chinese young adults transitioning to adulthood today are cultivated by both traditional Chinese values (e.g., collectivism, Confucian philosophy), as well as Western values (e.g., individualism, independence). The present study aimed to characterize emerging adults' perception of adulthood in China today in terms of: (1) the criteria for adulthood Chinese emerging adults considered important; (2) the relationships between subjective importance of adulthood status and status… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 54 publications
(79 reference statements)
2
17
0
Order By: Relevance
“…Finally, despite acceptable theoretical and empirical evidence supporting the use of the scale in the current study, the reliability of the adult identity scale was not particularly high. Future studies may replicate the findings with the objective measurements for adulthood, such as the Makers of Adulthood scale, which has been applied in the Chinese context to cross-validate the current finding ( Kuang et al, 2023 ).…”
Section: Limitations and Future Directionsmentioning
confidence: 71%
“…Finally, despite acceptable theoretical and empirical evidence supporting the use of the scale in the current study, the reliability of the adult identity scale was not particularly high. Future studies may replicate the findings with the objective measurements for adulthood, such as the Makers of Adulthood scale, which has been applied in the Chinese context to cross-validate the current finding ( Kuang et al, 2023 ).…”
Section: Limitations and Future Directionsmentioning
confidence: 71%
“…According to China's 2021 census, there are 316 million people aged 20–29 years. More than 70% of Chinese people aged 18–30 do not consider themselves to be adults (Kuang et al, 2023). This suggests that there may be a large number of emerging adults in China.…”
Section: Transition To Adulthoodmentioning
confidence: 99%
“…This percentage dropped to 25% in a 2013 survey (Nelson et al, 2013). A recent national survey of Chinese young people aged 18–30 showed that a large percentage do not see themselves as adults (84% of college students; 71% of non‐students) (Kuang et al, 2023). This suggests that emerging adulthood may be an increasingly prominent phenomenon in China.…”
Section: Transition To Adulthoodmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence supported that there may be significant differences in emerging adulthood in a culture that specifies structures roles and responsibilities to others (Arnett, 2000). As a result of globalization, Chinese young adults who transit to adulthood today are being exposed to a combination of traditional Chinese values such as collectivism and Confucian philosophy, as well as Western individualism (Kuang et al, 2023). In addition to independence, China young people generally believe that the benchmarks for adulthood include maintaining stable emotional regulation, going beyond egocentrism, showing more consideration and commitment to others, such as achieving financial independence and supporting parents, and avoiding behaviors that may tarnish the reputation of the family (Badger et al, 2006; Kuang et al, 2023; Nelson, 2004).…”
Section: Introductionmentioning
confidence: 99%